Vibration energy harvesting based monitoring of an operational bridge undergoing forced vibration and train passage. (June 2018) - Cahill, Paul; Hazra, Budhaditya; Karoumi, Raid; Mathewson, Alan; Pakrashi, Vikram
Highlights: Full-scale test on vibration energy harvesting based monitoring of bridges. Design and calibration of harvesters for full-scale monitoring. Direct use of harvested energy for signal processing and subsequent monitoring. Development and implementation of bespoke algorithms of system and even detection. Abstract: The application of energy harvesting technology for monitoring civil infrastructure is a bourgeoning topic of interest. The ability of kinetic energy harvesters to scavenge ambient vibration energy can be useful for large civil infrastructure under operational conditions, particularly for bridge structures. The experimental integration of such harvesters with full scale structures and the subsequent use of the harvested energy directly for the purposes of structural health monitoring shows promise. This paper presents the first experimental deployment of piezoelectric vibration energy harvesting devices for monitoring a full-scale bridge undergoing forced dynamic vibrations under operational conditions using energy harvesting signatures against time. The calibration of the harvesters is presented, along with details of the host bridge structure and the dynamic assessment procedures. The measured responses of the harvesters from the tests are presented and the use the harvesters for the purposes of structural health monitoring (SHM) is investigated using empirical mode decomposition analysis, following a bespoke data cleaning approach. Finally, the use of sequential Karhunen Loeve transforms to detect train passages during the dynamic assessment is presented. This study is expected to further develop interest in energy-harvesting based monitoring of large infrastructure for both research and commercial purposes.